Hydrogen role in the valorization of integrated steelworks process off-gases through methane and methanol syntheses - Matino, Ismael; Dettori, Stefano; Zaccara, Antonella; Petrucciani, Alice; Iannino, Vincenzo; Colla, Valentina; Bampaou, Michael; Panopoulos, Kyriakos; Rechberger, Katharina; Kolb, Sebastian; Hauser, Alexander; Wolf-Zoellner, Philipp; et al. (Materiaux et Techniques, 2022)
The valorization of integrated steelworks process off-gases as feedstock for synthesizing methane and methanol is in line with European Green Deal challenges. However, this target can be generally achieved only through process off-gases enrichment with hydrogen and use of cutting-edge syntheses reactors coupled to advanced control systems. These aspects are addressed in the RFCS project i(3)upgrade and the central role of hydrogen was evident from the first stages of the project. First stationary scenario analyses showed that the required hydrogen amount is significant and existing renewable hydrogen production technologies are not ready to satisfy the demand in an economic perspective. The poor availability of low-cost green hydrogen as one of the main barriers for producing methane and methanol from process off-gases is further highlighted in the application of an ad-hoc developed dispatch controller for managing hydrogen intensified syntheses in integrated steelworks. The dispatch controller considers both economic and environmental impacts in the cost function and, although significant environmental benefits are obtainable by exploiting process off-gases in the syntheses, the current hydrogen costs highly affect the dispatch controller decisions. This underlines the need for big scale green hydrogen production processes and dedicated green markets for hydrogen-intensive industries, which would ensure easy access to this fundamental gas paving the way for a C-lean and more sustainable steel production.
Created from Fastlane, WoS look-up